EFEKTIVITAS PEMANFAATAN QGIS DALAM MATERI TEKNOLOGI GEOSPASIAL UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS X - Aisyah, Nurul; Ernawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of using QGIS and to analyze the improvement of students’ cognitive learning outcomes in geospatial technology material. The research was motivated by the dominance of conventional learning methods that emphasize memorization rather than spatial analysis skills. This study used a quasi-experimental method with a non-equivalent control group design involving an experimental class and a control class. Data were collected through pre-test and post-test and analyzed using t-test and N-Gain. The results showed that the use of QGIS was effective in the learning process and significantly improved students' cognitive learning outcomes. The experimental class showed higher improvement compared to the control class. Thus, QGIS supports interactive and analytical geography learning.